Susceptibility tensor imaging of the kidney and its microstructural underpinnings - Xie, Luke (2014)
PURPOSE: The purpose of this study was to determine whether susceptibility tensor imaging (STI) could overcome limitations of current techniques to detect tubules throughout the kidney. METHODS: Normal mouse kidneys (n=4) were imaged at 9.4T using a 3D gradient multiecho sequence (55-micron isotropic resolution). Phase images from 12 orientations were obtained to compute the susceptibility tensor. Diffusion tensor imaging (DTI) with 12 encoding directions was compared with STI. Tractography was performed to visualize and track the course of tubules with DTI and STI. Confocal microscopy was used to identify which tubular segments of the nephron were detected by DTI and STI. RESULTS: Diffusion anisotropy was limited to the inner medulla of the kidney. DTI did not find a significant number of coherent tubular tracks in the outer medulla or cortex. With STI, we found strong susceptibility anisotropy and many tracks in the inner and outer medulla, and in limited areas of the cortex. CONCLUSION: STI was able to track tubules throughout the kidney, while DTI was limited to the inner medulla. STI provides a novel contrast mechanism related to local tubule microstructure and may offer a powerful method to study the nephron.